An improved mesh stiffness model for double-helical gear pair with spalling defects considering time-varying friction coefficient under mixed EHL. (March 2021) - Wang, Siyu; Zhu, Rupeng
Highlights: An improved TVMS calculation model of double-helical gear pair is proposed. The time-varying friction force under mixed EHL is coupled with the model. The influence of spalling defect with varying depth in spalled region on the TVMS is analyzed. The effect of dislocation phenomenon on the TVMS is investigated. Abstract: Based on "slice method", the improved time-varying mesh stiffness (TVMS) calculation model of double-helical gear pair with actual involute, and transition curve is proposed. The nonlinear contact stiffness, improved fillet-foundation stiffness, time-varying friction coefficient with mixed elastohydrodynamic lubrication (EHL) are considered in the model. Based on the improved model, the mesh stiffness of double-helical gear pair under spalling defects are obtained, in which the depth of spalled region is varied along action line, then the influence of spalling length, axial position, and dislocation phase on TVMS are investigated. The results of the improved mesh stiffness model were compared with the finite element method (FEM) results, the resulting coincidence illustrated the superiority of the improved model.